Vanishing bone disease (Gorham-Stout syndrome): A review of a rare entity. - Nikolaou, Vasileios S; Chytas, Dimitrios; Korres, Demitrios; Efstathopoulos, Nicolas (World J Orthop, 2014)
Vanishing bone disease (Gorham-Stout syndrome) is a rare entity of unknown etiology, characterized by destruction of osseous matrix and proliferation of vascular structures, resulting in destruction and absorption of bone. Despite the extensive investigation of the pathogenetic mechanisms of the disease, its etiology hasn't been clarified and several theories exist. The syndrome can affect one or multiple bones of the patient, including the skull, the upper and lower extremities, the spine and pelvis. The clinical presentation of a patient suffering from vanishing bone disease includes, pain, functional impairment and swelling of the affected region, although asymptomatic cases have been reported, as well as cases in which the diagnosis was made after a pathologic fracture. In this short review we summarize the theories regarding the etiology as well as the clinical presentation, the diagnostic approach and treatment options of this rare disease.